The influence of grain boundary area on the complexion time-temperature-transformation diagram of Eu-doped magnesium aluminate spinel. (15th March 2020) - Krause, Amanda R.; Kundu, Animesh; Kosasang, Onthida; Vinci, Richard P.; Harmer, Martin P.
Abstract: We demonstrate the sensitivity of complexion time-temperature-transformation (TTT)-diagrams to composition and grain size in Eu-doped MgAl2 O4 . 100 ppm and 500 ppm Eu-doped MgAl2 O4 undergo the same complexion transition, which causes abnormal grain growth, but exhibit different nucleation and grain growth rates. The Eu content per grain boundary area (Eu/GBA) was calculated for various heat treatments using a simple model based on average grain size. Despite their differences, a common Eu/GBA is calculated at the onset of abnormal grain growth. This common grain boundary excess has important implications for complexion TTT-diagrams and provides a new metric for predicting abnormal grain growth. Graphical abstract: Image, graphical abstract